2013
DOI: 10.1055/s-0033-1336775
|View full text |Cite
|
Sign up to set email alerts
|

Association between traffic-related air pollution, subclinical inflammation and impaired glucose metabolism: Results from the SALIA study

Abstract: Background: Environmental and lifestyle factors regulate the expression and release of immune mediators. It has been hypothesised that ambient air pollution may be such an external factor and that the association between air pollution and impaired glucose metabolism may be attributable to inflammatory processes. Therefore, we assessed the associations between air pollution, circulating immune mediators and impaired glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…followed up women who enrolled in the Canadian National Breast Screening Study ( n = 29,549), and the result showed a > 20% increase of diabetes mellitus per 10‐μg/m 3 increase in PM2.5 (prevalence ratio 1.28, 95% CI: 1.16–1.41). In addition, other cohort studies also reported relatively strong associations between exposure to PM2.5 and the incidence of diabetes mellitus (RRs from 1.25 to 1.42). Previous experimental studies showed that PM2.5 could lead to insulin resistance through oxidative damage, endothelial dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…followed up women who enrolled in the Canadian National Breast Screening Study ( n = 29,549), and the result showed a > 20% increase of diabetes mellitus per 10‐μg/m 3 increase in PM2.5 (prevalence ratio 1.28, 95% CI: 1.16–1.41). In addition, other cohort studies also reported relatively strong associations between exposure to PM2.5 and the incidence of diabetes mellitus (RRs from 1.25 to 1.42). Previous experimental studies showed that PM2.5 could lead to insulin resistance through oxidative damage, endothelial dysfunction and inflammation.…”
Section: Discussionmentioning
confidence: 93%
“…The present meta‐analysis showed a deleterious effect of long‐term exposure PM2.5 on the incidence of type 2 diabetes mellitus. Several previous studies explored the associations between PM2.5 with incident type 2 diabetes mellitus, diabetes mortality or prevalent impaired glucose metabolism. A large Canadian study, including more than 2 million participants, showed a strong positive association between PM2.5 and diabetes mortality.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported (Rioux et al, 2011), most earlier studies asked participants to abstain from taking their type 2 diabetes medications prior to biological sampling, did not report on, specifically evaluate, or have access to information on medication use (Teichert et al, 2013; O’Neill et al, 2005; O’Neill et al, 2007; Ostro et al, 2006; Schneider et al, 2008); or were conducted prior to the introduction of two of the oral medications evaluated here (Zanobetti and Schwartz, 2002; Bateson and Schwartz, 2004). Individuals with type 2 diabetes appear to be particularly vulnerable to air pollution (Gold, 2008) though particulate matter-induced CRP responses have not been consistent, perhaps due to the use of anti-inflammatory medications in this population (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 95%
“…The adverse response we observe here may be associated with disease severity, disease duration, or the interactive effects of insulin with traffic exposure. Insulin use is typically associated with longer disease duration, and for these individuals, other indicators of diabetes progression such as vascular dysfunction, may be modifying the response to traffic exposure (Barzilay et al, 2001; Teichert et al, 2013; O’Neill et al, 2005; O’Neill et al, 2007; Stewart et al, 2010). …”
Section: Discussionmentioning
confidence: 99%